IMPROVING THE SECOND-GRADE ELEMENTARY STUDENTS’ LEARNING OUTCOMES ON THE SUBJECT MATTER OF MULTIPLICATION USING DORAEMON POCKET MEDIA - Fadilla Diah Winta Utami; Asri Susetyo Rukmi; Catur Agustina Candra Dewi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses the improvement of the second-grade students’ learning outcomes at SDN Lakarsantri I/472 Surabaya in Mathematics learning subject on multiplication and division using Doraemon Pocket media. The research method used was classroom action research (CAR) in the form of cycles, which consist of action plans, implementation of actions, observation, and reflection. Data were collected by using instruments in the form of test sheets to measure students’ achievement. The analysis results indicate that there is increasing activity and learning achievement in mathematics about multiplication in class II students at SDN Lakarsantri I/472 Surabaya. It is evidenced by the results of research data processing that indicate increasing students’ activity and learning achievement in cycle 2. In the pre-cycle, students' percentage scores reached 58%. After conducting treatment by applying Doraemon Pocket in cycle 1, it increased to 82%. And in cycle 2, it increased to 92%. Thus, it can be concluded that Doraemon Pocket media can improve the students’ learning achievement in class II on the subject matter of multiplication.